2006
DOI: 10.2353/ajpath.2006.051272
|View full text |Cite
|
Sign up to set email alerts
|

Chronically Increased Transforming Growth Factor-β1 Strongly Inhibits Hippocampal Neurogenesis in Aged Mice

Abstract: There is increasing evidence that hippocampal learning correlates strongly with neurogenesis in the adult brain. Increases in neurogenesis after brain injury also correlate with improved outcomes. With aging the capacity to generate new neurons decreases dramatically, both under normal conditions and after injury. How this decrease occurs is not fully understood, but we hypothesized that transforming growth factor (TGF)-beta1, a cell cycle regulator that rapidly increases after injury and with age, might play … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
116
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(130 citation statements)
references
References 79 publications
10
116
2
Order By: Relevance
“…Overexpression of TGF-b1 in old mice inhibited the proliferation of early precursor cells (Buckwalter et al 2006).…”
Section: Mechanisms Underlying the Age-related Decline In Adult Neuromentioning
confidence: 98%
“…Overexpression of TGF-b1 in old mice inhibited the proliferation of early precursor cells (Buckwalter et al 2006).…”
Section: Mechanisms Underlying the Age-related Decline In Adult Neuromentioning
confidence: 98%
“…However, after brain injury TGF-β is also responsible for deposition of extracellular matrix proteins that contribute to glial scar formation (Logan et al, 1994(Logan et al, , 1999a which retards neuronal regeneration (McKeon et al, 1995;Windle et al, 1952) and increases the induction of traumatic epilepsy after brain injury (Hoeppner and Morrell, 1986;Tian et al, 2005). Additionally, TGF-β may suppress the early stages of neurogenesis (Buckwalter et al, 2006;Wachs et al, 2006), which may reduce the regenerative capacity of the brain. Thus, targeting TGF-β to enhance recovery from traumatic injury becomes complex because of these multiple and sometimes conflicting functions.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, we and others reported that intracerebroventricular infusions of TGF-b into the rat brain or overexpression of TGF-b in transgenic mice resulted in a marked downregulation of cell proliferation and neurogenesis in the hippocampus. 57,58 Moreover, levels of TGF-b are known to be increasing in the brain along with ageing. 59,60 Additional experiments targeting specifically the individual signaling systems are required to elucidate in the age-dependent loss of fluoxetine activities on neurogenesis.…”
mentioning
confidence: 99%